"You Are a Part of the Solution": Negotiating Gender-Based Violence and Engendering Change in Urban Informal Settlements in Mumbai, India. (October 2017) - Chakraborty, Proshant; Daruwalla, Nayreen; Jayaraman, Anuja; Pantvaidya, Shanti
This article explores how women front-line workers engage with domestic and gender-based violence in the urban informal settlements of Dharavi in Mumbai, India. We conducted in-depth interviews with 13 voluntary front-line workers, along with ethnographic fieldwork in Dharavi, as a part of a pilot study. Our findings contribute to literature on context-specific approaches to understanding gender-based violence and "models" to prevent domestic violence in urban micro-spaces. Furthermore, we also discuss notions of "change" ( badlaav ) that the front-line workers experience. Finally, this article presents implications for socially engaged ethnographic research, as well as contextual and grounded insights on ways to reduce gender-based and domestic violence.